Application of Total Quality Management (TQM) Requirements in Risk Management in Construction Projects in Iraq (Journal of Engineering, 2016)
Total quality management  considers one of the modern scientific entrances  which practiced by productivity service organizations alike to provide appropriate quality required outputs according to the needs and desires of customers manage , enable the organization seeking to continue and grow in light of the increasing competition from the satisfy and provide the appropriate total quality management requirements whenever led to face risks that they may have  in a manner in which they can be addressed and find ways to avoid them in the future when repeated.                                                                                                                                              The research has consist of two main parts firstly have included a review of the most important concepts of total quality management in addition to the concept of risk analysis and management in construction projects and how to apply the concept of total quality management in the risk analysis and management. Second part included the practical part of the research, which was open and closed questionnaire for experts in the construction industry to obtain required informations for the application of total quality management requirements in risk  management in construction projects in Iraq.                                                                                    One of the main findings of the research is that top management support has a high impact on risk management in addition to continuous improvement, training and education, while the participation of all employees in the organization and constant stimulation and focusing on the customer as one of the total quality management requirements had a moderate impact on risk management.